THE INFLUENCE OF FORGIVENESS AND DEMOCRATIC PARENTING STYLE ON BULLYING BEHAVIOR IN YOGYAKARTA HIGH SCHOOL STUDENTS - Baroroh, Nurin; nana, Pramudita; khoirunnisa, nikki; Putri (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
The purpose this study to examine the influence of forgiveness and authoritative (democratic) parenting style on the behavior of bullying in high school students Y in Yogyakarta grade 11. This study uses quantitative approach to test the hypotheses. Result after screening for receive student with authoritative parenting style are 106 people. Data collection is done by using three types of scale, namely the scale of forgiveness, parenting scale, and the scale of bullying behavior. Democratic parenting contribute to effective contribution of 19% and 48% forgiveness of these results indicates the tendency of low bullying behavior to be gained is greatly influenced by forgiveness.